2023
DOI: 10.1097/md.0000000000033882
|View full text |Cite
|
Sign up to set email alerts
|

Anterior fontanel size in Korean nursery newborns and clinical implications of large anterior fontanel: A retrospective cohort, observational study

Abstract: Anterior fontanel (AF) sizes in newborns are influenced by ethnicity, gender, genetics, nutrition, and other pathological conditions. However, AF sizes in recent Korean newborns have not been reported yet. Thus, this study aimed to understand variation in AF size and clinical implications of large AF sizes in newborns. This cohort study was conducted on nursery newborns born at a University Hospital between September 2019 and August 2020. AF size was measured at 24 to 48 hours after birth. Newborns with a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…In a recent study, birth weight and head circumference were found to be risk factors for anterior fontanelle width. 25 Duc and Largo 4 also found that the percentage of closed fontanelles was higher in boys than in girls, although not statistically significant. Similar findings regarding the higher percentage of closed fontanelles in boys compared to girls, without statistical significance, have been documented in other studies as well.…”
Section: Discussionmentioning
confidence: 89%
“…In a recent study, birth weight and head circumference were found to be risk factors for anterior fontanelle width. 25 Duc and Largo 4 also found that the percentage of closed fontanelles was higher in boys than in girls, although not statistically significant. Similar findings regarding the higher percentage of closed fontanelles in boys compared to girls, without statistical significance, have been documented in other studies as well.…”
Section: Discussionmentioning
confidence: 89%